Treatment of the Carotid In-stent Restenosis: A Systematic Review - Huang, Hao; Wu, Lingshan; Guo, Yinping; Zhang, Yi; Zhao, Jing; Yu, Zhiyuan; Luo, Xiang (Frontiers in Neurology, 2021)
Background and Purpose—In-stent restenosis (ISR) after carotid artery stent (CAS) is not uncommon. We aimed to evaluate therapeutic options for ISR after CAS. Methods—We searched PubMed and EMBASE until November 2, 2020 for studies including the treatment for ISR after CAS. Results—In total, 35 studies, covering 1374 procedures in 1359 patients, were included in this review. Most cases (66.3%) were treated with repeat CAS (rCAS), followed by percutaneous transluminal angioplasty (PTA) (17.5%), carotid endarterectomy (CEA) (14.3%), carotid artery bypass (1.5%), and external beam radiotherapy (0.4%). The rates of stroke & TIA within the postoperative period were similar in three groups (PTA 1.1%, rCAS 1.1%, CEA 1.5%). CEA (2.5%) was associated with a slightly higher rate of postoperative death than rCAS (0.7%, P = 0.046). Furthermore, the rate of long-term stroke & TIA in PTA was 5.7%, significantly higher than rCAS (1.8%, P = 0.036). PTA (27.8%) was also associated with a significantly higher recurrent restenosis rate than rCAS (8.2%, P = 0.002) and CEA (1.6%, P < 0.001). The long-term stroke & TIA and recurrent restenosis rates showed no significant difference between rCAS and CEA. Conclusions—rCAS is the most common treatment for ISR, with low postoperative risk and low long-term risk. CEA is an important alternative for rCAS. PTA may be less recommended due to the relatively high long-term risks of stroke & TIA and recurrent restenosis.